2023
DOI: 10.3390/cancers15153919
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor Beta and Epithelial to Mesenchymal Transition Alter Homologous Recombination Repair Gene Expression and Sensitize BRCA Wild-Type Ovarian Cancer Cells to Olaparib

Cai M. Roberts,
Mehida Rojas-Alexandre,
Ruth E. Hanna
et al.

Abstract: Epithelial ovarian cancer (EOC) remains the most lethal gynecologic malignancy, largely due to metastasis and drug resistant recurrences. Fifteen percent of ovarian tumors carry mutations in BRCA1 or BRCA2, rendering them vulnerable to treatment with PARP inhibitors such as olaparib. Recent studies have shown that TGFβ can induce “BRCAness” in BRCA wild-type cancer cells. Given that TGFβ is a known driver of epithelial to mesenchymal transition (EMT), and the connection between EMT and metastatic spread in EOC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…SMAD2 gene, targeted by three DE miRNAs, was found to be enriched in the pathways controlled by TGFβ receptors. Findings by Roberts et al revealed that treatment with TGFβ induced EMT and downregulated homologous recombination repair protein, resulting in resensitization of HGSOC cells to olaparib in vitro [61]. Here, we showed that enriched signaling by FGFR1, EGFR, PDGF as well as VEGFR2 mediated cell proliferation was associated with genes encoding trinucleotide repeat-containing gene 6A protein (TNRC6A) and calmodulin 1 (CALM1), targeted by three and two DE miRNAs, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…SMAD2 gene, targeted by three DE miRNAs, was found to be enriched in the pathways controlled by TGFβ receptors. Findings by Roberts et al revealed that treatment with TGFβ induced EMT and downregulated homologous recombination repair protein, resulting in resensitization of HGSOC cells to olaparib in vitro [61]. Here, we showed that enriched signaling by FGFR1, EGFR, PDGF as well as VEGFR2 mediated cell proliferation was associated with genes encoding trinucleotide repeat-containing gene 6A protein (TNRC6A) and calmodulin 1 (CALM1), targeted by three and two DE miRNAs, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…Recent studies in breast and ovarian cancer have shown that EMT can, in certain circumstances, be a marker of drug sensitivity rather than resistance. As we and our colleagues recently observed, in ovarian cancer this may be a case of stemness and EMT working in opposite directions, with both very epithelial and very mesenchymal cells exhibiting drug resistance [119] (Figure 3). Furthermore, how mesenchymal markers correspond to therapeutic efficacy in sarcomas remains to be seen.…”
Section: Discussionmentioning
confidence: 80%
“…Despite the many cases described here in which EMT or its constituent transcription factors are associated with drug resistance, there are some cases in which EMT is a marker of therapeutic vulnerability. For instance, we recently described a reduction in homologous recombination repair protein expression in multiple models of ovarian cancer EMT that sensitized the cells involved to treatment with cisplatin, the PARP inhibitor olaparib, and the DNA-PK inhibitor Nu-7441 [119]. This was based on prior work in which chemoresistant ovarian cancer CSCs were shown to be epithelial, while fast-dividing mesenchymal-like progeny was sensitive [120].…”
Section: Emt and Drug Sensitivitymentioning
confidence: 99%